2000
DOI: 10.1007/pl00004023
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital Symptoms and Resulting Discomfort in Non-Institutionalized Dutch Women Aged 50–75 Years

Abstract: The aim of this study was to determine the prevalence of urogenital symptoms in non-institutionalized Dutch women aged 50-75 years, and the degree of discomfort suffered as a result. A questionnaire was sent to 2157 women, a sample representative of the female population aged 50-75 years with respect to age, marital status, level of education and menopausal age. The usable response was 81.6% (n = 1761). The overall prevalence of vaginal dryness, soreness and dyspareunia was 27%. The prevalence of micturition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 19 publications
2
46
2
3
Order By: Relevance
“…Symptoms recur more severely with each subsequent pregnancy and ultimately may result in permanent disability. The results of the longitudinal studies performed during pregnancy and after childbirth suggest that pregnancy may weaken or cause disruption of the pelvic musculofascial structures which support the continence mechanism or may uncover a genetic predisposition to incontinence [25,42,50,53,79]. Incontinence during pregnancy or immediately after childbirth was found to be highly correlated with urinary incontinence in later life [24,55,82].…”
Section: Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Symptoms recur more severely with each subsequent pregnancy and ultimately may result in permanent disability. The results of the longitudinal studies performed during pregnancy and after childbirth suggest that pregnancy may weaken or cause disruption of the pelvic musculofascial structures which support the continence mechanism or may uncover a genetic predisposition to incontinence [25,42,50,53,79]. Incontinence during pregnancy or immediately after childbirth was found to be highly correlated with urinary incontinence in later life [24,55,82].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The authors concluded that mixed incontinence may be over-reported in epidemiological surveys and a larger majority than hitherto reported may have pure stress incontinence. A few studies have shown that after menopause the relative proportion of urge incontinence increases with age, whereas the percentage of stress incontinence shows a slight but definite decrease [5,36,62,79,86].…”
Section: Type Of Urinary Incontinencementioning
confidence: 99%
See 3 more Smart Citations